PENGGUNAAN METODE EKSPERIMEN DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS IV SDN 03 V KOTO TIMUR KECAMATAN V KOTO TIMUR KABUPATEN PADANG PARIAMAN - Fitri, Asnita; Yuliar, Yuliar; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this study is to describe the improvement of learning outcomes of students in Natural Sciences using experimental methods in class IV SDN 03 V Koto East. The type of this research is Classroom Action Research (PTK) and using qualitative and quantitative approach. The subjects of this research are students of SDN 03 V Koto Timur class which amounted to 18 people. This study consists of 2 cycles. The research procedure consists of four stages: (1) planning, (2) implementation, (3) observation, (4) reflection. The results of this study using inquiry methods in Elementary School. The results of RPP assessment using Experimental Method in the cycle I 75% and in cycle II to 89.06%. Teacher aspect in cycle I 76,78% increase in cycle II become 91,06%. Aspects of students in the cycle I 74.99% to 89.28% in cycle II. The average of students' learning hasill in cycle I 70,23 and increase in cycle II to 83,49. Keywords – Understanding of sciences concepts, Experimental method